2017
DOI: 10.3390/ijerph14070748
|View full text |Cite
|
Sign up to set email alerts
|

Post-Disaster Food and Nutrition from Urban Agriculture: A Self-Sufficiency Analysis of Nerima Ward, Tokyo

Abstract: Background: Post-earthquake studies from around the world have reported that survivors relying on emergency food for prolonged periods of time experienced several dietary related health problems. The present study aimed to quantify the potential nutrient production of urban agricultural vegetables and the resulting nutritional self-sufficiency throughout the year for mitigating post-disaster situations. Methods: We estimated the vegetable production of urban agriculture throughout the year. Two methods were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Despite the growing attention paid to the sharing economy and household food production, the non-market and non-monetized sharing of home-grown food has largely escaped scholars' attention [11]. There are several studies which revealed the multidimensional roles of non-market food provision through home-gardens and community gardens in developed countries [12][13][14][15][16]. However, the existing literature has not examined the relationship between such sharing practices and landscape characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growing attention paid to the sharing economy and household food production, the non-market and non-monetized sharing of home-grown food has largely escaped scholars' attention [11]. There are several studies which revealed the multidimensional roles of non-market food provision through home-gardens and community gardens in developed countries [12][13][14][15][16]. However, the existing literature has not examined the relationship between such sharing practices and landscape characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…These areas remain vulnerable today and were often built up with low-quality housing (e.g., wooden rental houses-Moku-chin, in Japanese), lacking infrastructure, and with narrow roads [61]. Local municipalities (e.g., Nerima ward) have been exploring the potential to utilize the remaining UA in these areas for low-cost disaster preparedness purposes (evacuation and food provisioning) [23].…”
Section: Land Use Patternsmentioning
confidence: 99%
“…The dataset on professional UA (vegetable fields and orchards) was retrieved (2015) and primary data of the spatial locations and areas of hobby UA types was developed in the present study. This was conducted according to the method developed by Sioen et al [23,37] and described below, updated, and refined according to the latest satellite imagery (2015-2016) and objective of the present study.…”
Section: Current Urban Agricultural Land Usementioning
confidence: 99%
See 2 more Smart Citations